TAXATION CHALLENGES IN NIGERIA IN 21ST CENTURY: A REVIEW OF RELATED LITERATURE (Journal of Contemporary Issues in Accounting, 2022)
A well-functioning Revenue system is a necessary condition for strong, reliable, sustainable and inclusive economic development strategies. The correlation between tax-payers and tax authorities are the conceptualized tax policy and framework on rights, obligations, filling of returns, Assessments, collections, appeal and petitions cases, penalties, fines, refunds/payment procedures which have significant influence on revenue generation in Nigeria with fundamental short-coming or challenges. The concept of this paper was on a review of related literature and this article provides an inside challenges between tax-payers on assessment (IMF, 2006), the public Expenditure and Financial Accountability Assessment (PEFA) and the Tax Administration Diagnostic Assessment Tool (TADAT) will provide a standard and gauge that reveals the strengths and weakness of the tax administration and the disputes/conflict resolution between stakeholders on value Added Tax (VAT) federal government of Nigeria vs Rivers and Lagos States government on who should collect VAT? The answer is simple, VAT collection is done by federal government by law and also international best practice the Appeal court sitting in Abuja, set aside the judgment made on High court Port Harcourt- River state (2021). The Nigeria tax reforms needs to be treated with care or caution, being mindful of the current economic situation and standard of living, any proposal to this effect must meet international standard of the developed economy with consent of the stakeholders to support a strong citizen-state relationship that has underpinning effects; effective, efficient, economy, accountable and stable government in provision of potential benefits like infrastructures, security and basic needs to the citizenry in order to have a workable and sustainable tax system.
Keywords: Taxation; challenges; 21 century; tax system; tax administration; tax deposited